A new species of Oligosoma (Squamata: Scincidae) from the northern North Island, New Zealand - Barr, Benjamin P.; Chapple, David G.; Hitchmough, Rodney A.; Patterson, Geoff B.; Board, Ngātiwai Trust (Zootaxa, 2021)
New Zealand is home to a diverse cool temperate assemblage of skinks, with 60+ identified taxa (genus Oligosoma Girard), of which only 50 have been formally described. Here we describe a new species (Oligosoma kakerakau sp. nov.) from Bream Head Scenic Reserve, near Whangārei Heads, Northland. This species is considered to be conspecific with a single specimen (Oligosoma “Whirinaki”) previously reported (in 2003) from Whirinaki Te Pua-a-Tāne Conservation Park 370 km further south. Oligosoma kakerakau sp. nov. can be distinguished from all other members of the genus by a combination of a distinctive “teardrop” marking below the eye, a distinctive mid-lateral stripe, and the colouration and pattern on its ventral surface. Our phylogenetic analyses indicate that Oligosoma kakerakau sp. nov. is most closely related to O. zelandicum (Gray), and more distantly to O. striatum (Buller) and O. homalonotum (Boulenger). Sea level changes during the Pliocene, such as the formation of the Manawatū Strait, may have contributed to the divergence between Oligosoma kakerakau sp. nov. and O. zelandicum. We discuss the distribution, ecology and conservation of Oligosoma kakerakau sp. nov., and outline future research and conservation priorities for the species.